Excellent mechanical and corrosion properties of austenitic stainless steel with a unique crystallographic lamellar microstructure via selective laser melting - Sun, Shi-Hai; Ishimoto, Takuya; Hagihara, Koji; Tsutsumi, Yusuke; Hanawa, Takao; Nakano, Takayoshi (Scripta materialia, 2019)
We first developed a unique “crystallographic lamellar microstructure” (CLM), in which two differently oriented grains appear alternately, in a 316L stainless steel specimen via selective laser melting technology. The CLM was composed of major 〈011〉 grains and minor 〈001〉 grains aligned along the build direction, which stemmed from vertical and approximately ±45° inclined columnar cells formed in the central and side parts of melt-pools, respectively. The development of CLM was found to largely improve the material properties via the strengthening of the product, simultaneously showing superior corrosion resistance to commercially obtained specimens. [Display omitted]